Potential effects of fermented moringa (Moringa oleifera) leaf extract to increase the color brightness of the Oranda goldfish (Carassius auratus) - SITI UMAIYAH; ACHMAD NOERKHAERIN PUTRA; MUH. HERJAYANTO; MAS BAYU SYAMSUNARNO (Nusantara Bioscience, 2023)
Abstract. Umaiyah S, Putra AN, Herjayanto M, Syamsunarno MB. 2023. Potential effects of fermented moringa (Moringa oleifera) leaf extract to increase the color brightness of the Oranda goldfish (Carassius auratus). Nusantara Bioscience 15: 288-296. Moringa (Moringa oleifera Lam.) leaf extract serves as a natural reservoir of carotenoids, prominently ?-carotene, effectively employed to augment the color quality of ornamental fish. This study aimed to evaluate the potential effects of adding fermented moringa leaf extract to feed to enhance the color vibrancy of Oranda goldfish (Carassius auratus (Linnaeus, 1758)). Moringa leaves were also fermented using Aspergillus niger Tiegh. at a dosage of 0.5 g/100 g for 48 hours, followed by extraction using 70% ethanol. Four doses of fermented moringa leaf extract (0, 40, 50, 60 mL/kg) with three replications were added to a commercial feed using the coating method. The results showed that the carotene in fermented moringa leaf extract is 94.22 ppm/50 mL. Adding moringa leaf extract to the feed enhanced the Oranda goldfish's brightness and color diversity. The addition of fermented moringa leaf extract at a dose of 60 mL/kg led to the highest color diversity values on the body (57.81%), caudal (71.71%), and head (71.13%) compared to other treatments. Moringa leaf extract did not affect growth rate, survival, blood profile, and water quality parameters for maintaining Oranda goldfish. The extract from A. niger had the potential to be used in the cultivation of Oranda goldfish, and the addition of 60 mL/kg achieved the best color brightness and diversity.